(untitled) (World Bulletin of Public Health, 2022)
The main focus of this study was to assess knowledge of workplace stress and application of workplace stress reduction strategies among nurses in the University of Uyo teaching hospital, Uyo. Cross-sectional survey design was adopted for this work. The area covered by the researcher was University of Uyo Teaching Hospital, Uyo. The target population for this study was 529 nurses in UUTH Administration Office); comprising male and female nurses between 27 to 50 years of age working at the Hospital. Simple random sampling technique was used to select 250 (two hundred and fifty) respondents consisting of nurses working at the Teaching Hospital from six Departments who constituted the sample size used for the study. The instrument used in this study for data collection was a questionnaire titled " The Health Work Questionnaire” (HWQ). In order to establish both the face and content validity of the research instruments, the drafted instrument was given to the researcher’s supervisor and an expert in Physical and Health Education Department, University of Uyo, Uyo and from Educational Foundation, Guidance and Counseling Department, University of Uyo, Uyo. To validate it. The Measure of Central Tendency (mean and percentage) was used to obtain the Criterion Mean. The Chi-square statistical analysis was used to test the hypotheses, set at probability alpha level of 0.05. From the result it was observed that there is significant difference in the extent of knowledge and awareness of workplace stress among nurses at UUTH, Uyo. It was observed that there is significant difference in the extent of presence of workplace stressors among nurses at the UUTH, Uyo. Finally, the result proved that there is significant difference in the extent of application of individual workplace reduction strategies among nurses at the UUTH, Uyo. The study concluded that nurses are knowledgeable and aware of stress at workplace, stressors like overloading work, negative supervisory relationship and feeling irritated at workplace are among the factors determining workplace stress. One of the recommendations made in the study was that employer’s efforts at UUTH, Uyo to decrease the determinants of stress in the workplace can increase nurses’ productivity and so should be encouraged.